1995
DOI: 10.1093/infdis/172.3.638
|View full text |Cite
|
Sign up to set email alerts
|

Increased Human Immunodeficiency Virus (HIV) Type 1 DNA Content and Quinolinic Acid Concentration in Brain Tissues from Patients with HIV Encephalopathy

Abstract: Levels of human immunodeficiency virus type 1 (HIV-1) DNA and quinolinic acid were examined in areas of the central nervous system (CNS) and lymphoid organs (LN) from 5 AIDS patients with no clinically apparent CNS compromise (group I), 7 with CNS opportunistic diseases (group II), and 8 with HIV encephalopathy (group III). The brains from patients with HIV encephalopathy not only contained higher levels of HIV-1 DNA (cerebrum, P < .01; cerebellum, P < .05) as assessed by quantitative polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 44 publications
4
30
1
Order By: Relevance
“…Elevated levels of quinolinic acid, in particular, have been consistently observed in vivo in the cerebrospinal fluid and brain parenchyma of patients with ADC (1,19,36). The severity of neurological symptoms has been correlated with the increase in quinolinic acid levels in the brain in the simian immunodeficiency virus model of ADC (21).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Elevated levels of quinolinic acid, in particular, have been consistently observed in vivo in the cerebrospinal fluid and brain parenchyma of patients with ADC (1,19,36). The severity of neurological symptoms has been correlated with the increase in quinolinic acid levels in the brain in the simian immunodeficiency virus model of ADC (21).…”
mentioning
confidence: 90%
“…Macrophages activated with HIV-1 or HIV-1 envelope glycoprotein (gp120) contribute to the production of a number of putative neurotoxins including glutamate (8), arachidonic acid metabolites (12,13), nitric oxide (12), platelet-activating factor (13), tumor necrosis factor alpha (12,13,38), and quinolinic acid (30,36). Elevated levels of quinolinic acid, in particular, have been consistently observed in vivo in the cerebrospinal fluid and brain parenchyma of patients with ADC (1,19,36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty of measuring QUIN in CNS tissues has hampered our ability to examine this question more directly. However, direct measurement of QUIN in CNS tissues from HIV-infected humans at autopsy revealed higher levels in the CNS of patients with HIV encephalopathy or opportunistic infections than in patients with no clinically apparent CNS dysfunction [49]. A recent in vitro study found QUIN to be produced by HIVinfected monocytes at significantly higher levels on immune activation with lipopolysaccharide or interferon-␥, suggesting that viral infection, as well as immune activation, are key determinants of QUIN production [50].…”
Section: Quinmentioning
confidence: 99%
“…A recent study has shown that VIP can also prevent a similar NMDA-induced, nitric oxide-dependent injury in lung tissue (63). Elevated levels of quinolinate (64,65) and toxic products (including cytokines) released from macrophages/microglia have also been associated with increased levels of gp120 and may play a role in gp120 toxicity (55,59,60,66,67).…”
Section: Discussionmentioning
confidence: 99%